ANALISIS KECELAKAAN KERJA DENGAN MENGGUNAKAN METODE FAULT TREE ANALYSIS (Studi Kasus PT. XYZ) - Muhammad Nur; Maimunah Harahap; Aris Fiatno (Jurnal Teknik Industri Terintegrasi, 2019)
PT. XYZ is a leading industry in the field of CPOB-based medicine (How to Make Drugs). Implementation of Practice Work at PT. XYZ aims to understand the scope, to understand the implementation of the work system as well as to occupational health and safety, to know the flow of production, to know the issues that are occurring, and to make improvements for the company. Problems found in PT.XYZ. The pearl of pearl Farms is Unsafe Behavior which is a work ethic that does not prioritize occupational health and safety. The solution to the problem is to use the Fault Tree Analysis (FTA) method with the result of paying close attention to environmental conditions on the production floor, providing K3 training to the workers and rewarding those who obey and sanction the violators, creating a display , provide tools and encourage employees to follow the company's SOP.